Observation of Atmospheric Neutrino Events with the AMANDA Experiment - Karle, Abrecht (arXiv, 1999)
A first analysis of the AMANDA-B 10-string array data is presented. A total of 113 days of data from its first year of operation in 1997 have been analyzed. High energy neutrinos generate upward moving muons. Cosmic ray muons penetrating the ice sheet to a depth of 2000 m are the major source of background. We discuss the method used to reject the background of approximately 0.5*10^9 downgoing muons and leave 17 upward going events. The neutrino candidates are discussed and compared with expectations. : 5 pages, Latex2.09, uses sprocl.sty and epsf.sty, 6 postscript figures. Talk presented at the 17th International Workshop on Weak Interactions and Neutrinos, Cape Town, South Africa, January 1999